The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/bjs.9589
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after parathyroidectomy for lithium-induced hyperparathyroidism

Abstract: Surgery provided a safe and effective management option for patients with LiHPT in this series, with a long-term cure rate of well over 80 per cent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The definitions used and the length of exposure to lithium can at least partly, explain the discrepancies. Though the majority of these patients (approximately 50 %) have a single parathyroid adenoma, there is a higher incidence of multiple adenomas compared with the ordinary pHPT patient cohort [ 33 36 ]. Many hypotheses on the underlying mechanism of LAH have been proposed including: increased threshold of the calcium-sensing receptor, increased secretion of the PTH, decrease of calcium uptake, inhibition of action of glycogen synthase kinase 3b and reduction of PTH gene transcription [ 37 ].…”
Section: Pathogenesis Of Sporadic Multiglandular Diseasementioning
confidence: 99%
“…The definitions used and the length of exposure to lithium can at least partly, explain the discrepancies. Though the majority of these patients (approximately 50 %) have a single parathyroid adenoma, there is a higher incidence of multiple adenomas compared with the ordinary pHPT patient cohort [ 33 36 ]. Many hypotheses on the underlying mechanism of LAH have been proposed including: increased threshold of the calcium-sensing receptor, increased secretion of the PTH, decrease of calcium uptake, inhibition of action of glycogen synthase kinase 3b and reduction of PTH gene transcription [ 37 ].…”
Section: Pathogenesis Of Sporadic Multiglandular Diseasementioning
confidence: 99%
“…Nevertheless, in the biggest study concerning LIHPT so far, published by Järhult et al in 2010 (n = 71), only 45 % of the patients with LIHPT had single adenomas and the cure rate was not more than 58 % [21]. Several other studies also showed high rates of MGD among patients with LIHPT [14,[20][21][22][23][24] while others found singu-lar adenomas in the majority of cases [25,26]. They go in line with the present study, in which out of five patients with LIHPT who underwent primary surgery only one had four gland hyperplasia (20 %) and no one had any recurrent or persistent disease.…”
Section: Discussionmentioning
confidence: 97%
“…While some studies reported high rates of MGD in LIHPT ranging from 52 and 75 % [14,[20][21][22][23][24], others reported single parathyroid adenomas in the majority of cases [25,26]. Furthermore, some claimed high rates of persistent/recurrent disease after surgery [21,24].…”
Section: Contextmentioning
confidence: 99%
“…Carchman et al [ 9 ], however, state that there is no significantly increased risk for multiglandular disease (MGD) in lithium-treated patients. On the other hand, numerous studies present higher frequencies of MGD ranging from 25 to 83% [ 10 , 26 , 33 37 ]. The surgical results in the present study further confirm these latter results with MGD occurring in five of seven patients (70%) (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%